Physical characteristics of nipah fruit flour (Nypa fruticans Wurmb) using Response Surface Methodology (RSM) - R Agustina; D Dinaroe; M Yasar; K Anwar; Sarni; Foo@Jurry bt. F Michae (IOP Publishing Ltd, 2025)
Aceh is one of the regions that produce nipa fruit. The people of Aceh primarily use young nipa fruit as an ingredient in refreshing beverages. In contrast, mature nipa fruit is often discarded despite its numerous potential benefits as a food source, such as for producing flour, dodol (a type of confection), and candied fruit. This study aims to determine the physical characteristics of nipa flour by varying the drying temperature and grinding time, and to identify the optimal conditions for producing nipa fruit flour based on moisture content and yield, using Response Surface Methodology (RSM). The study employs a Central Composite Design (CCD) experimental approach, facilitated through XLSTAT software. The physical analysis of nipa flour focuses on moisture content and yield. The results indicate that drying temperature and grinding time significantly affect nipa flour's moisture content and yield. The data were analyzed using ANOVA, revealing significant values of 0.039 (p < 0.05) for moisture content, and 0.0001 (p < 0.005) for yield, with an R² value for yield. Based on its physical properties, the optimal formulation for nipa flour involves a drying temperature of 41.20°C and a grinding time of 3.32 minutes, predicted to yield a moisture content of 11% and an approximate yield of 41.62%.